Financial Risks and Derivative Use of Non-financial Companies in Turkey - Yeşildağ, Eser (Frontiers in Applied Mathematics and Statistics, 2019)
Companies are exposed to many risks in their life. Derivatives are one of the tools that companies commonly use in order to mitigate these risks. The fluctuations in the markets in recent years have increased companies' need to use derivatives. For this reason, the importance of derivatives is increasing every day. The purpose of this study is to ascertain the financial risks which arise from the activities of non-financial companies in BIST 100 index operating in Turkey and the derivatives used in the management of these risks. In addition, this study aims to determine the differences between companies using derivatives and those not using derivative products. Therefore, the year-end financial reports of 58 companies, which were continuously in the BIST100 index between 2013 and 2018 were analyzed. The study results showed that the risks that the companies were exposed to included credit risk, liquidity risk, interest risk, currency risk and other risks and only half of the companies, on average, used derivatives in the management of these risks. In addition, it was observed that companies rather hedged themselves against currency risks through futures contracts and used more derivatives in the transportation and energy sectors. Besides, it is seen that the companies using derivative products are big and low liquid companies.